Articulation of Muslim Subjectivity in Search the Ideal Type of Muslim Women: Ayu Momalula’s Counseling Da’wah on Instagram - Rezki Putri Nur Aini; Ratno Lukito (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2024)
Religious discussions among previous socio-religious scholars used to focus more on authority, righteousness, commodification efforts, and the pursuit of financial gains by religious figures. However, this seems less relevant in today's digital age, where people can access and share religious knowledge from various sources. This article aims to explore this phenomenon by examining the approach of a da'wah influencer, Ayu Momalula. She presents counseling da'wah content as a form of self-expression, creating an ideal Muslim woman figure for her social media followers. Using an exploratory qualitative method and online ethnographic approach, primary data was obtained from interviews via WhatsApp and Zoom, as well as from observation of content on her Instagram accounts and books. The study argues that Ayu Momalula's counseling da'wah activities aim to establish herself as an ideal Muslim woman, supporting her authority as a religious micro-celebrity. The article analyzes her subjectivity as a Muslim women micro-celebrity, highlighting her representation of a pious wife and modern mompreneur through content visualization on social media. This study suggests that Ayu Momalula actively promotes productivity in both work and preaching to her specific target audience.